L’analyse linguistique des enjeux de connaissance dans le discours scientifique - Fanny Rinck (Revue d'anthropologie des connaissances)
The litterature review presented here is aimed to provide a background for linguistic analysis of scientific discourse (and/or academic discourse) and its knowledge issues. It is first shown how science studies have been interested in analysing scientific activity through the signs and texts it produces. The second part focuses on the linguistic analysis of scientific discourse and what it can say about the scientific activity. In the conclusion are discussed the various ways to adress knowlede issues of scientific discourse.